KARAKTERISTIK PARKIR DI KAMPUS IBI DARMAJAYA LAMPUNG - Syarkowi, Muhar; Munawaroh, Ai Siti (Jurnal Arsitektur dan Perencanaan (JUARA), 2019)
The purpose of study is to determine the parking characteristics and analyze the standards of parking space requirements and plan an effective parking pattern at IBI Darmajaya Lampung.Primary data obtained from field surveys and secondary data obtained from Public Relation.The results of the study showed maximum parking accumulation was 21 cars and 272 motorbikes with an average accumulation of cars of 19.73 / hour and motorcycles of 194.87/ hour. The average duration is 3.5 cars / hour and 65 motors/ hour. The maximum parking volume is 16 cars and 160 motorbikes. PTO for cars is 0.15 vehicles / plot / hour and 0.23 vehicles / plot / hour. The maximum parking index is 130% car cars and 148,9% motorcycles.Parking Needs for 105 plot cars and 238 plot motorcycles. An effective parking pattern is an angled parking pattern of 90 Â° and 60 Â°. This parking pattern has a capacity of more than 13 cars and 50 motorcycles compared to parallel parking patterns.Â